2017
DOI: 10.1002/clc.22681
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and cardiovascular disease in the geriatric population

Abstract: There has been little focus on the effects of alcohol on the elderly. Although the cardiovascular benefits of moderate alcohol consumption could be of the greatest benefit in this group, so might be the detrimental effects of abuse. In this article, we review available data on the effects of alcohol consumption on cardiovascular disease, cardiomyopathy, arrhythmias, hypertension, and vascular function in older adults. Alcohol consumption has increased in the US population age 65 years and older in the last dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Moreover, our study focused on the association between drinking frequency and all-cause mortality. However, alcohol consumption also has other impacts, such as on morbidity [21, 31] and hospitalization [97]. Thus, if we had used other health outcomes such as use of health care resources, we might have found an association between frequent drinking and the outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our study focused on the association between drinking frequency and all-cause mortality. However, alcohol consumption also has other impacts, such as on morbidity [21, 31] and hospitalization [97]. Thus, if we had used other health outcomes such as use of health care resources, we might have found an association between frequent drinking and the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy alcohol consumption has also been found to be related to increased mortality from cardiovascular disease [23] and alcohol-related cancer [21, 22]. Furthermore, heavy alcohol consumption is associated with a number of medical conditions, such as heart failure [31], hypertension [31], cardiac arrhythmia [21], stroke [21], liver disease [21], cancer [21], dementia [32] and mental health problems (depression, suicide, cognitive impairment) [3335] all of which might increase mortality risk. In general, comparison of mortality in relation to alcohol consumption in studies of middle- aged and older adults are complicated due to the use of different alcohol measures, definitions and reference categories [1016, 2230].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of stroke, studies showed a decreased risk of stroke associated with mild alcohol exposure (<15 g/day), while moderate drinkers showed no difference [ 31 ] compared to non-drinkers. Furthermore, it was reported that in older patients heavy alcohol increased their risk of heart failure and hypertension, whereas moderate alcohol drinking did not show negative effects on cardiovascular function [ 34 ]. Similarly, a meta-analysis and review by Briasoulis et al, 2102, indicated an increased risk of hypertension in men with heavy alcohol exposure, which was less obvious in moderate and low drinkers.…”
Section: Systemic Effects Of Alcoholmentioning
confidence: 99%
“…The cardiovascular health effects of alcohol have classically been described as having a J-shaped curve, in which low-to-moderate consumers present less risk than lifetime abstainers, and heavy drinkers show the highest risk [5,19,20,[22][23][24][25]. Alcohol intake benefits not only healthy individuals, but also patients with established CVD [3,5].…”
Section: Introductionmentioning
confidence: 99%